Rotational Coherence Spectroscopy and Excited-State Dynamics of Tolane and its Van Der Waals Complexes with Argon and Nitrogen. Issue 1 (1994) - Ohline, Shane M.; Romascan, Joann; Felker, Peter M.
Abstract : We report the results of rotational coherence spectroscopy on tolane, tolane–Ar, and tolane–N2 . The results on tolane are consistent with a planar geometry for the species. They also provide information about the symmetries of excited vibronic states in the species. The results on the van der Waals complexes provide significant experimental constraints on where the small species bind to tolane. In addition, we report the observation of a rapid excited-state decay process in the complexes and discuss the possible nature of this process.